CONTROL OF TRANSPORTATION OF SPARE PARTS OF VEHICLES - Yuriy Petrovich Preobrazhenskiy; Vera Nikolaevna Kostrova; Alexander Alexeevich Plotnikov (International Journal of Advanced Studies, 2020)
The paper discusses the problem associated with the supply of spare parts of vehicles. Its solution is based on a simulation approach. The results of the simulation are presented.